2012
DOI: 10.1007/s00464-012-2148-0
|View full text |Cite
|
Sign up to set email alerts
|

Description of a novel approach for intraperitoneal drug delivery and the related device

Abstract: This device and the related approach significantly improve both distribution and penetration of a test substance into the peritoneal cavity in a large animal model. This might be a significant progress in treating intraperitoneal disease, in particular peritoneal carcinomatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
135
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(139 citation statements)
references
References 18 publications
2
135
0
2
Order By: Relevance
“…In vivo experiments on the living animal are probably the best model for optimizing therapeutic [5,6], as compared to ex vivo experiments [4] or experiments using cadavers [7]. Although the use of live animals continues to be necessary to protect human animal health, it is desirable to replace such procedures by other methods not entailing the use of live animals [8].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo experiments on the living animal are probably the best model for optimizing therapeutic [5,6], as compared to ex vivo experiments [4] or experiments using cadavers [7]. Although the use of live animals continues to be necessary to protect human animal health, it is desirable to replace such procedures by other methods not entailing the use of live animals [8].…”
Section: Discussionmentioning
confidence: 99%
“…Some experimental studies have shown higher drug penetration in tumoural nodes with higher and controlled intra-abdominal pressure. Solass et al [6] showed higher drug penetration in the intra-abdominal pressure group called therapeutic pneumoperitoneum. Facy et al [7] showed a different Oxaliplatin penetration under different thermal conditions and intra-abdominal pressure in a porcine model.…”
Section: Discussionmentioning
confidence: 99%
“…The working mechanism of PIPAC is based on local administration of cytotoxic agents on the tumoral surface in the abdominal cavity. The aerosol form accomplishes homogeneous drug distribution [30], while it is believed that the high intra-abdominal pressure enhances tissue penetration and antitumor effects [31,32]. As a consequence, a low dose of chemotherapy can be used, causing low systemic drug uptake and toxicity [29,33].…”
Section: Current Clinical Management Of Pcmentioning
confidence: 99%